Evolocumab, a PCSK9‐Monoclonal Antibody, Rapidly Reverses Coronary Artery Endothelial Dysfunction in People Living With HIV and People With Dyslipidemia. Issue 14 (21st July 2020) - Leucker, Thorsten M.; Gerstenblith, Gary; Schär, Michael; Brown, Todd T.; Jones, Steven R.; Afework, Yohannes; Weiss, Robert G.; Hays, Allison G.
Abstract : Background: PCSK9 (proprotein convertase subtilisin/kexin type 9) is well recognized for its important role in cholesterol metabolism. Elevated levels are associated with increased cardiovascular risk and inhibition with PCSK9 antibodies (PCSK9i) lowers cardiovascular events in patients with coronary artery disease. PCSK9 levels are also elevated in people living with HIV (PLWH) and those with dyslipidemia. Because increased PCSK9 in PLWH is associated with impaired coronary endothelial function, a barometer of coronary vascular health, we tested the hypothesis that PCSK9i improves impaired coronary endothelial function in dyslipidemia without coronary artery disease and in PLWH with nearly optimal/above goal low‐density lipoprotein cholesterol levels. Methods and Results: We performed a single‐center study in 19 PLWH and 11 with dyslipidemia to evaluate the effects of the PCSK9i evolocumab on coronary endothelial function using cine 3T MRI to noninvasively measure coronary endothelial function, assessed as the changes in coronary cross‐sectional area and coronary blood flow from rest to that during isometric handgrip exercise, a known endothelial‐dependent vasodilator. Before evolocumab, there was a decrease or no coronary vasodilation and no increase in coronary blood flow (the normal responses) to isometric handgrip exercise in either group. Following 6 weeks of evolocumab, 480 mg q4 weeks, the % cross‐sectional area changes from rest to isometric handgrip exercise were +5.6±5.5% and +4.5±3.1% in the PLWH and dyslipidemia groups, respectively, both P <0.01 versus baseline. Improved cross‐sectional area was paralleled by a significant coronary blood flow improvement in both groups. Conclusions: To our knowledge, these data represent the first evidence that PCSK9 inhibition improves coronary artery health in PLWH and people with dyslipidemia. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03500302.